Analisis Siklus Pendapatan terhadap Pengendalian Internal pada PT Pelangi Wisata Madaniah - Syamsinar; Samsinar; Afiah, Nur (Bongaya Journal of Research in Accounting (BJRA), 2025)
This study aims to analyze the revenue cycle at PT Pelangi Wisata Madaniah, particularly its role in supporting internal control and the challenges encountered in its implementation. The subject of this research is the Accounting Information System, with a focus on the revenue cycle and internal control. Data were collected through interviews and documentation, then analyzed using a descriptive qualitative approach. The findings indicate that cash sales in the revenue cycle have been carried out quite effectively, as reflected in the completeness of documents and procedures. However, there are several weaknesses, such as the absence of an internal audit function, accounting records that are not fully in accordance with standards, and the lack of an integrated system. These conditions have led the revenue cycle to be less than optimal in supporting internal control, as shown by overlapping functions, manual recording, and limited supervision. The main challenges faced by the company include the absence of functional separation between sales, cash, and accounting, as well as reliance on Microsoft Excel, which is prone to input errors and data loss.